The Pacific Islands - Moshe Rapaport (University of Hawai'i Press, 2013)
themes of scholarly inquiry and has long engaged academic interest alongside systematic approaches to scientific understanding. While populations and land areas of the Pacific Islands are relatively small, this vast archipelagic world is in many ways unique and offers special opportunities for regional study. Courses focusing on the Pacific Islands are offered at many universities, and Pacific Island Studies programs have been established. There is currently a vital need for a basic reference on Pacific Islands environment and society, which this book aims to fill. The revaluation of place in the social sciences and humanities offers a contemporary rationale for the study of regions. As political boundaries have become permeable to economic, demographic, and cultural flows, distant places and regions come increasingly into view. Yet local institutions and cultures endure, providing the reassurances of stability, tradition, authenticity, and care. Modernization, long seen as transcending place and region, is conditioned by locale (Daniels 1992). Even in Hawai‘i and New Zealand (sometimes considered part of the Pacific Rim) there is keen awareness of the historical and current linkages with other parts of the Pacific Islands region. Regions are at best models of the real world. This is particularly so for the Pacific Islands, which range from far-flung coral atolls to large islands with fast-flowing rivers and high mountain ranges; from cultures where traditional chiefs still hold power to those where indigenous languages have become endangered. The boundaries of regions are notoriously difficult to define. Yet like all models, regions allow useful generalizations. Like other forms of education, regional awareness is an essential mode of dispelling ignorance, misunderstanding, mistrust, and conflict (Johnston 1990).